(untitled) (Menara Perkebunan, 2026)
Honey is recognized for its high nutritional and functional value, yet it remains vulnerable to contamination by antibiotic residues such as tetracycline when beekeeping practices are not properly managed. Post-harvest pasteurization is widely utilized to improve honey safety and quality. This study examined the effects of pasteurizing honey at 60°C for 10, 20, or 30 minutes on tetracycline and oxytetracycline residue levels, as well as on the physicochemical, microbiological, and antioxidant properties of acacia honey (Apis mellifera). Honey samples were artificially contaminated with antibiotics at 1 µg/g and analyzed using high-performance liquid chromatography (HPLC). Pasteurization at 60°C reduced oxytetracycline residues by approximately 33% (P<0.01). Pasteurization also decreased moisture content and diastase enzyme activity, while acidity increased with longer heating durations. Hydroxymethylfurfural levels remained very low (<1 mg/kg), indicating minimal thermal damage. Reducing sugar and sucrose levels were largely unchanged, total plate count (TPC) decreased slightly but not significantly, and yeasts and molds were undetectable after 10 minutes of pasteurization. Antioxidant activity showed a slight, non-significant reduction, whereas flavonoid content declined substantially due to heat exposure. In summary, pasteurization at 60°C effectively reduces antibiotic residues and microbial presence in honey, but also affects certain quality parameters, particularly diastase enzyme activity, acidity, and flavonoid content.